Metode, Tujuan, Dan Prinsip-Prinsip Komunikasi Islam - Efendi, Erwan; Bagus, Den; Yanti, Juwita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research was conducted to find out how communication is in an Islamic perspective. The use of research methods seen from the type of research that is using the method used in this research is a qualitative method with a library research approach. The results of this study are that the communication in question is Islamic communication, namely communication with al-karimah or ethical morals. Communication with good morals means communication that originates from the Al-Quran and hadith (sunnah of the Prophet). As for the objectives of Islamic communication, one of them is giving good news and threats, inviting those who are good and preventing evil, giving warnings to those who are negligent, advising and admonishing. Principles are guidelines that make humans interpret an event, in Islamic communication covering all Islamic teachings, including aqidah (iman), sharia (Islam), and morals (ihsan). Regarding the method (kaifiyah), various guidelines are found in the Koran and Al-Hadith so that communication can run well and be effective. In various literatures on Islamic communication we can find at least six types of speech styles or talks qaulan sadidan, qaulan balighan, qaulan masurran, qaulan layinan and qaulan ma'rufan.